Hubungan Pengawas Minum Obat dan Tipe Dukungan Keluarga Terhadap Kepatuhan Minum Obat Pasien Tuberkulosis Paru di Kota Banda Aceh - Zulheri Zulheri; Fadli Syahputra; Lidyawati Lidyawati (Journal of Pharmaceutical and Health Research, 2021)
Banda Aceh City is the capital of Aceh Province with the highest number of lung tuberculosis cases. This can be seen from the increase in the incidence of pulmonary tuberculosis in Banda Aceh City. The purpose of this study was to determine the relationship between the role of PMO and family support with pulmonary anti tuberculosis (OAT) drugsThis type of research is analytic descriptive with Cross Sectional Design and the object of research is 128 people with pulmonary TB in Banda Aceh City. The study was conducted for 3 months from August-November 2018 located in all Puskesmas working areas of the Banda Aceh City Health Office data analysis using logistic regression tests. Results PMO supervision, 57.8% received instrumental support, 53.1% received information support, 56.2% received valuation support, 64.0% received emotional support, 63.2% received spiritual support, 50.7% received financial support. statistical results obtained there is a PMO relationship (OR = 18.5 P-Value = 0,000) there is information support (OR = 5.4, P-value = 0.002), there is emotional support (OR = 3.54, P-Value = 0.027), there is support financial (OR = 0 .22, P-Value = 0.018), no instrumental support (OR = 2.5, P-Value = 0.050), no valuation support (OR = 1.22, P-Value = 0.664), no support spiritual (OR = 0.55, P-Value = 0.247)